Teknologi Pengolahan Yoghurt Sebagai Diversifikasi Produk Susu Kambing pada Kelompok Ternak Desa Wonoasri Kecamatan Tempurejo Kabupaten Jember - Utami, Merry Muspita Dyah; Pantaya, Dadik; Subagja, Hariadi; Ningsih, Niati; Dewi, Aryanti Candra (Universitas Sebelas Maret, 2020)
Title:Â Yogurt Processing Technology as a Diversification of Goat Milk Products in the Livestock Group of Wonoasri Village, Tempurejo District, Jember RegencyCommunity service activities aim to empower the Peranakan Ettawa (PE) goat group of Wonoasri village, Tempurejo Sub-District, Jember Regency with education on processing goat milk into yoghurt. The prospect of marketing goat milk yoghurt has a market opportunity in the community, increasing the selling price of goat milk, and being a solution to the utilization of unsold goat milk. Community service activities are carried out from June to November 2019. The results obtained by the farmer group can make yoghurt processed products and implement yoghurt business management. This activity concludes that all members of the livestock group can make yoghurt according to procedures and can implement yoghurt business management as a sustainable business. The preferred yoghurt is yoghurt made with a concentration of 1% with a strawberry flavor variant. Yoghurt making activities can increase farmers income.